2019
DOI: 10.3389/fpls.2019.01290
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Cucumber Onto Pumpkin Induced Early Stomatal Closure by Increasing ABA Sensitivity Under Salinity Conditions

Abstract: During early periods of salt stress, reduced stomatal opening can prevent water loss and wilting. Abscisic acid (ABA) signal plays an important role in this process. Here, we show that cucumber grafted onto pumpkin exhibits rapid stomatal closure, which helps plants to adapt to osmotic stress caused by salinity. Increased ABA contents in the roots, xylem sap, and leaves were evaluated in two grafting combinations (self-grafted cucumber and cucumber grafted onto pumpkin rootstock). The expression levels of ABA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Notably, the significantly higher root biomass of Atlante under salinity ( Figure 1 b) would allow better access to water resources as it has been shown in open-field crops with modulated CK biosynthesis by transgenic rootstocks [ 29 , 56 ]. Furthermore, ABA sensitivity has been demonstrated to improve the water status in grafted tomato [ 14 , 57 ], pepper [ 24 ], and cucumber [ 25 ] plants under salinity. Thus, the coordinated modulation of ABA and CKs levels of pepper plants grafted onto Atlante would help to regulate stomatal aperture [ 58 ] and/or density [ 59 ], maintaining stomatal conductance ( Figure 2 f), transpiration rate ( Figure 2 g), and photosynthesis ( Figure 2 e) under salinity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the significantly higher root biomass of Atlante under salinity ( Figure 1 b) would allow better access to water resources as it has been shown in open-field crops with modulated CK biosynthesis by transgenic rootstocks [ 29 , 56 ]. Furthermore, ABA sensitivity has been demonstrated to improve the water status in grafted tomato [ 14 , 57 ], pepper [ 24 ], and cucumber [ 25 ] plants under salinity. Thus, the coordinated modulation of ABA and CKs levels of pepper plants grafted onto Atlante would help to regulate stomatal aperture [ 58 ] and/or density [ 59 ], maintaining stomatal conductance ( Figure 2 f), transpiration rate ( Figure 2 g), and photosynthesis ( Figure 2 e) under salinity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that grafting vegetable crops onto tolerant rootstocks can improve global plant performance and final productivity under different abiotic stress conditions [ 10 , 11 , 13 , 14 , 15 , 16 ]. Particularly, improved growth and yield stability responses mediated by the rootstock under salinity conditions have been described in different vegetable crops, such as tomato [ 17 , 18 , 19 , 20 ], pepper [ 21 , 22 , 23 , 24 ], cucumber [ 25 , 26 ], watermelon [ 27 ], and others [ 28 ]. These rootstock-mediated responses have been associated with a better status of the photosynthetic apparatus and increased sink activity [ 8 , 22 ], regulation of ion homeostasis [ 17 , 20 , 21 , 26 ], and modulation of hormonal balance [ 14 , 17 , 18 , 25 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some metabolites, mRNAs, and proteins were reported to produce in the rootstock spread/transport/migrate via cell-to-cell to the ground of the grafted vegetables [ 39 , 40 ]. Pumpkin rootstocks are widely used in cucumber grafting cultivation due to their strong vigor, including enhancing photosynthesis, keeping stability of plasma membrane, and so on [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Considering both carbon metabolism in photosynthesis existing in both Csa move-down and Cmo move-up mRNAs, we assumed that Csa mRNAs relating to carbon fixation produced in cucumber aboveground transport into pumpkin roots via phloem firstly.…”
Section: Discussionmentioning
confidence: 99%
“…Cucumber ( Cucumis sativus L.) (Csa) is a major vegetable crop grown under protected cultivation in China. To protect against biotic and abiotic stresses, cucumber seedlings are mainly cultivated by heterografting onto commercial pumpkin ( Cucurbitea moschata ) (Cmo) rootstocks [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, the mechanisms by which grafting alters plant growth and development, especially how mRNA signals exchanged between scion and rootstock affect adaption and tolerance to environmental conditions, are still unknown.…”
Section: Introductionmentioning
confidence: 99%